2022
DOI: 10.4103/ijo.ijo_1133_21
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of dry eye disease in N95 versus surgical face mask wearers during COVID-19

Abstract: Purpose: Investigating the effect of different face masks on dry eye disease (DED) among healthcare workers during the COVID-19 pandemic. Methods: This was a comparative, cross-sectional study. Participants were included into two groups: group 1 (n = 30) wore surgical masks, and group 2 (n = 30) wore N95 masks with face shields. Demographic and ocular surface disease index questionnaires (OSDI) were performed. In addition, Tear break-up time (TBUT), corneal and conjunct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 21 publications
1
11
0
Order By: Relevance
“…Whereas in another study, the OSDI score was higher for female participants in comparison to male participants [ 23 ]. In a similar study on HCWs, no significant differences were observed in DED between genders [ 24 ]. The OSDI values showed a significant difference between age groups, with the age group <40 years having a high median value.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Whereas in another study, the OSDI score was higher for female participants in comparison to male participants [ 23 ]. In a similar study on HCWs, no significant differences were observed in DED between genders [ 24 ]. The OSDI values showed a significant difference between age groups, with the age group <40 years having a high median value.…”
Section: Discussionmentioning
confidence: 99%
“…The OSDI score was highest (67.24) in 53 participants wearing N95 masks without respirators, compared to 48.29 in 54 participants wearing surgical masks in our study. In a cross-sectional study on HCWs for assessment of DED in N95 versus surgical FM wearers during COVID‑19, authors observed a significant increase in the OSDI score in the N95 mask group versus the surgical mask group [ 24 ]. But if we look into the theory proposed, it is surprising as N-95 FM is more air-sealed, so the chances of air skipping must be less as compared to surgical or other masks.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When the effect of different types of masks on the ocular surface were compared, Azzam et al found that N95 masks caused significantly more dryness according to decreasing TBUT and fluorescein staining [ 53 ].…”
Section: Effects Of Face Mask Use On the Ocular Surface Of Healthy In...mentioning
confidence: 99%
“…Face masks induce dry eye occurs due to blowing of the air upwards when breathing out and due to the limited movement of the lower eyelid which accelerates the evaporation of the tears and leads to the onset or the worsening of the symptoms related to the dry eye disease. [10][11][12] The direct airflow from exhaled air will certainly leads towards the instability, enhanced evaporation and hyperosmolarity which leads towards a decline in the turn over of the tears which ultimately leads towards drying of cornea due to face mask. [13][14][15][16] Severity in the symptoms of mask induced ocular dryness are correlated to the thickness of the lipid layer of the tear film.…”
Section: Introductionmentioning
confidence: 99%